Time-varying intensity of ventilatory inefficiency and mortality in patients with acute respiratory distress syndrome - Lianlian Jiang; Hui Chen; Wei Chang; Qin Sun; Xueyan Yuan; Zongsheng Wu; Jianfeng Xie; Ling Liu; Yi Yang (Annals of Intensive Care)
Abstract Background The association between bedside ventilatory parameters—specifically arterial carbon dioxide pressure (PaCO2) and ventilatory ratio (VR)—and mortality in patients with acute respiratory distress syndrome (ARDS) remains a topic of debate. Additionally, the persistence of this association over time is unclear. This study aims to investigate the relationship between 28-day mortality in ARDS patients and their longitudinal exposure to ventilatory inefficiency, as reflected by serial measurements of PaCO2 and VR. Methods We conducted a secondary analysis of four randomized controlled trials (FACTT, ALTA, EDEN, and SAILS) from the ARDS Network. All included patients were intubated and received mechanical ventilation. Patients were excluded if they underwent extracorporeal life support or were on mechanical ventilation for less than one day. The primary outcome was 28-day mortality. Bayesian joint models were employed to estimate the strength of associations over time. Results A total of 2,851 patients were included in our analysis. The overall 28-day mortality rate was 21.3%, with a median duration of invasive mechanical ventilation of 9 days (IQR: 4–28 days). After adjustment, each daily increment in PaCO2 (HR 1.008, 95% CI 0.997–1.018) was not associated with mortality, while a daily increment in VR (HR 1.548, 95% CI 1.309–1.835) was associated with increased mortality. This association persisted during the prolonged stages (Days 0–23) of mechanical ventilation. Furthermore, a significant increase in the risk of death was related to daily exposure to VR > 2 (HR 1.088 per day, 95% CI 1.034–1.147) and its cumulative effect (HR 1.085 per area, 95% CI 1.050–1.122), whereas PaCO2 was found to be insignificant. Conclusion VR, which reflects ventilatory inefficiency, should be closely monitored during invasive mechanical ventilation. Cumulative exposure to high intensities of VR may be associated with increased mortality in patients with ARDS.